2014
DOI: 10.1016/j.nbd.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular amyloid and the neuronal origin of Alzheimer neuritic plaques

Abstract: Genetic analysis of familial forms of Alzheimer's disease (AD) causally links the proteolytic processing of the amyloid precursor protein (APP) and AD. However, the specific type of amyloid and mechanisms of amyloid pathogenesis remain unclear. We conducted a detailed analysis of intracellular amyloid with an aggregation specific conformation dependent monoclonal antibody, M78, raised against fibrillar Aß42. M78 immunoreactivity colocalizes with Aß and the carboxyl terminus of APP (APP-CTF) immunoreactivities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 36 publications
9
102
1
Order By: Relevance
“…In addition, phosphorylation of APP – which occurs to a large extent at the ER [20], and is increased in AD [39] and stress [40] – could favor APP cleavage at the slightly higher pH in the ER lumen. Recent studies reported that, in the aging brain, APP fragments accumulate in perinuclear compartments in the soma [41, 42]. In cultured neuronal cells, bona fide APP fragments are occasionally detected in a perinuclear compartment of the ER that associates with neurofilaments [43] (Fig.…”
Section: Where Is App Cleaved In Physiological and Pathological Condimentioning
confidence: 99%
“…In addition, phosphorylation of APP – which occurs to a large extent at the ER [20], and is increased in AD [39] and stress [40] – could favor APP cleavage at the slightly higher pH in the ER lumen. Recent studies reported that, in the aging brain, APP fragments accumulate in perinuclear compartments in the soma [41, 42]. In cultured neuronal cells, bona fide APP fragments are occasionally detected in a perinuclear compartment of the ER that associates with neurofilaments [43] (Fig.…”
Section: Where Is App Cleaved In Physiological and Pathological Condimentioning
confidence: 99%
“…Most Aβ peptides in human brain tissue are either 40 or 42 residues in length (Aβ40 and Aβ42), typically produced in an approximate 5:1 abundance ratio, but with more pronounced aggregation of Aβ42 (Gravina et al 1995). Aβ aggregation is traditionally considered to be an extracellular process, although there is also evidence that Aβ aggregation can occur intracellularly (Pensalfini et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Understanding the downstream effects of intracellular A β oligomers accumulation in AD-affected neurons is crucial as they are shown to lead to profound deficits in memory and cognitive function [29, 30], and are likely to play a major role in the earliest phase of AD pathogenesis [23, 27]. As reported by different groups including us, the liberation of Ca 2+ from intracellular stores is seen as a possible mechanism for the cytotoxicity of intracellular A β oligomers [8, 3133].…”
Section: Discussionmentioning
confidence: 99%
“…Thus the oligomer concentrations used in our experiments are in reality much smaller than the numbers give in Table 4. Furthermore, the intracellular accumulation of A β 42 can be two to three folds higher than the extracellular concentration [27, 5661]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation